Evaluation of the effectiveness of intra-articular administration of highly purified hyaluronic acid in knee osteoarthritis in real clinical practice - V. A. Nesterenko; E. I. Byalik; M. A. Makarov; S. A. Makarov; V. E. Byalik; A. A. Roskidailo; V. N. Amirdzhanova; M. R. Nurmukhametov; A. M. Lila (Современная ревматология, 2021)
Knee osteoarthritis (kOA) is a common cause of turning for medical advice, associated with chronic pain and disability. One of the methods of OA treatment is the local administration of hyaluronic acid (HA) drugs.Objective: to evaluate the effectiveness of intra-articular (IA) administration of highly purified HA (Armaviskon Plus) in kOA.Patients and methods. The study group consisted of 58 patients (74.1% women and 25.9% men, aged 59.5±11.8 years) with kOA, experiencing moderate/severe pain (≥40 mm on a visual analogue scale, VAS). All patients received IA injection of HA Armaviskon Plus (2 ml of a 1.5% solution), 2 injections with an interval of 7 days. The effectiveness criterion was the dynamics of pain at rest and during movement (VAS 0-100 mm) and the function of the knee joint according to a numerical rating scale (NRS 0-100 points) 2 weeks, 1 and 3 months after administration of therapy.Results and discussion. During the treatment, there was a significant improvement in all indicators. The average severity of pain during movement at baseline, after 2 weeks, 1 and 3 months was 50 [40; 60], 30 [20; 40], 15 [0; 30], 20 [0; 30] mm (p<0.001), at rest 20 [10; 40], 5 [0; 20], 0 [0; 20], 10 [0; 20] mm (p<0.05) by VAS. The average values of functional indicators were 40 [10; 60], 10 [0; 40], 20 [0; 40], 10 [10; 30] scores according to the NRS. A decrease in non-steroidal anti-inflammatory drugs demand was recorded: 67.1% of patients were initially taking them, after 3 months – 36.1% (p<0.001). No serious adverse reactions were noted.Conclusion. IA administration of HA is an effective and safe method for the treatment of kOA. Armaviskon Plus, a highly purified high-molecular- weight HA drug, has shown good results in pain reduction and improvement of function in knee OA as well as a favorable safety profile, which makes it possible to recommend its use in real clinical practice.